Reading comprehension skills included in Arabic language subject for fourth grade of basic education in Syria - رهام قاسم; ديوب , وائل; شاهين , رباب رمضان (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aimed to the extent that reading comprehension skills were included in the Arabic language subject for the fourth grade of the basic education stage، and to achieve this aim، the researcher prepared a list of reading comprehension skills that should be included in the Arabic subject for the fourth grad, and a content analysis tool for use in analyzing the Arabic language course, The descriptive and analytical method is used to answer the study questions. The results of the research showed the percentage of recurrence of each level of reading comprehension, where the Conclusion level came in first place with a percentage (96.64%), and in second place is the direct level with a percentage (92.85%), while the creative level got a percentage (39.45%), then The critical level with (32.13%) percentage, and the sentiment level came in the last place with a rate of (7.14%) Where levels of reading comprehension in the Arabic language subject of the fourth grade were sequenced according as follow: the conclusion level, the direct level, the creative level, the critical level, the sentiment level